Tourist satisfaction in aesthetic qualities of islands in east coast region in Malaysia - Lokman, Ainun Khadijah; Saad, Mazni; Yuliviona, Reni; Nasrah, Rasidah (Perpustakaan Negara Malaysia, 2021)
This study deals with aesthetic qualities in island tourism on the East Coast of Malaysia. The beauty of the island is undeniable, which the record of tourist arrivals is very encouraging. However, the island's main strengths have yet to be discovered. It is unclear what is the primary aesthetic qualities contribute to tourist satisfaction. Factors that entice tourists to return must be understood in order for their loyalty to continue to visit. Hence, this study investigates the relationship between aesthetic qualities (cleanliness, scenery, art/architecture, and genuineness) and tourist Satisfaction. This research aims to determine whether aesthetic qualities affect tourist satisfaction in Malaysia's East Coast islands. This study used the questionnaire survey and collected 150 responses (39% response rate) from tourists who had visited any of Malaysia's East Coast islands in the past three years. Through IBM-SPSS version 24, the multiple regression analysis reveals that all aesthetic qualities (cleanliness, scenery, art/architecture, and genuineness) contributed to tourist satisfaction when visiting the East Coast region's islands. The findings aimed to raise public awareness about the importance of the sustainability concept while also benefiting a large number of stakeholders.